IMPLEMENTATION OF THE ROLE OF HUMAN RESOURCE DEVELOPMENT AS A STRATEGIC PARTNER, AGENT OF CHANGE AND INNOVATION - Nor Rozi (OIKONOMIA: Journal of Economics and Management Science, 2023)
Companies are faced with rigorous challenges by meeting the ever-increasing needs and expectations of markets and customers. To ensure competitiveness and success, organizational managers need to accept innovation as a key organizational element. However, the main driver of innovation is human resources and to be successful it is necessary to support, plan and maintain a culture of innovation. Human resources are of little concern to people because the results of investment in human resources are difficult to quantify, difficult to see and are long-term in nature HR practitioners must have knowledge of the change process, so that they can fully understand the framework and plan for change and must have compatible leadership skills to ensure transition to increase productivity. This research is a research with a qualitative approach to the literature study or literature review used in this study. Literature review is used by looking for articles related to innovation-based HR development originating from published books, journals and all forms of writing related to the above matters. The conclusion from this literature review is that companies big or small need change agents when they want to change their structure, introduce new products/services or new technologies. A change agent helps an organization to shift to a new way of doing things and therefore we can say that a change agent is any person with the power and skills to facilitate and guide change efforts